The Role of Strategic Analysis in Improving The Financial Performance of Banks Field Study of The Private Banks on The Syrian Coast - مرهج منذر; حموي طارق (Latakia University Journal - Economic and Legal Sciences Series, 2021)
The research aims to determine the role of the strategic analysis in improving the financial performance of the private banks on the Syrian Coast. The researcher has used the descriptive analytical method. The data collection has been based on the questionnaire, where the researcher distributed 210 questionnaires to the CEOs, their deputies, their assistants, financial directors and internal auditors of 14 banks listed on the Damascus Stock Exchange. 129 questionnaires have been retrieved, including 22 incomplete questionnaires and 107 analyzable ones. The researcher has analyzed the data using the SPSS 20 statistical analyses program, depending on a group of statistical tests and repetitions, the most important of which are: measures of dispersion and centralization, t-Test, ANOVA difference test, and the Pearson correlation test. The research has concluded that the strategic analysis has the role in improving the financial performance of the private banks under study. The research came out with a set of recommendation the most important of which is that enhancing the implementation of strategic planning and activating the strategic analysis in banks due to their positive role in improving financial performance